Investigating the impacts of plausible Canadian policies and their supporting mechanisms on export-based regional air pollution in China: A cement manufacturing case study - Darren Brown; Rehan Sadiq; Kasun Hewage (Canadian Science Publishing, 2018)
The Canadian Environmental Protection Act (CEPA) enables the Minister of Environment and Climate Change to develop policy to curtail international air pollution. However, regional air pollution generated during the manufacturing of products outside of Canada is not addressed in CEPA. Using cement manufacturing in China as a case study, three policy options were devised to manage export-based regional air pollution. The options investigated included Policy 1-an open border with direct support for domestic cement manufacturers, Policy 2-a restricted border with no support for domestic cement manufacturers, and Policy 3-a selective border with partial support for domestic cement manufacturers. An analytic hierarchy process, in conjunction with the three actionable solidarities of cultural theory, was applied to the policy options and their supporting mechanisms. Results indicated that Policy 3 was strongly favoured (52.5%), followed by Policy 2 (33.4%), with Policy 1 being the least favoured (14.2%). Regarding policy mechanisms, a verification process was preferred by all three solidarities. From the standpoint of a universal approach to trade it is recommended that an air quality agreement between China and Canada under CEPA be established with a framework to eventually incorporate environmental production declarations. With respect to cement exports, it is recommended that manufacturers in China provide emissions intensities and winter smog assessments.